Comparative Analysis of Motivation Theories - Zsuzsanna Kispál-Vitai (International Journal of Engineering and Management Sciences, 2016)
The aim of the article is to compare motivation theories from the view of general psychology and work psychology. The research was done by using secondary sources and by analyzing motivation from both views. The difference between the two lines lies in outcome orientation. Psychology is more descriptive work psychology tends to focus on the results of the motivation process. In comparison, both have their values. The relevance of the research is to provide a theoretical basis for improving the development of more relevant motivation theories.